Branding Produk Label Kamasan Sebagai Upaya Pengembangan Daya Tarik Pemasaran pada UMKM Rengginang di Kelurahan Pakistaji Wonoasih Kota Probolinggo - Dyah Ayu Perwitasari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2021)
Lately, Indonesia has been shocked by the existence of a pandemic that has yet to be controlled, namely the Covid-19 pandemic. This certainly has a significant impact on people's lives, especially the people of Pakistaji Village, Wonoasih District, which is one of the areas where the majority of the population works as farmers. However, to meet economic needs, the community also uses Micro, Small and Medium Enterprises (UMKM) as a secondary source of income in meeting their household needs. One of them is UMKM which is managed by Mrs. Suryani, which produces rengginang in it. UMKMintervention in developing the community's economy is very necessary considering that the community's economy has decreased people's purchasing power or there are obstacles to the distribution of goods and services from producers to consumers and obstacles are significantly affected due to the effect of the PSBB policy during the current Covid-19 pandemic. The results of this study indicate that the efforts made by Wonoasih District KKN students in empowering Rengginang UMKMare providing guidance related to packaging labels on Mrs. Suryani's rengginang products, the establishment of Rengginang UMKM nameplates, and marketing which are expected to be able to differentiate from other packaging products and increase power. competitiveness in the MSME business. Rengginang Ms. Suryani.Keyword : Pakistaji,Empowerment, Rengginang UMKM, Covid-19, Packaging Labels